The ethics of unilateral implantable cardioverter defibrillators and cardiac resynchronization therapy with defibrillator deactivation: patient perspectives. Issue 8 (3rd December 2016) - Daeschler, Margaret; Verdino, Ralph J.; Kirkpatrick, James N.
Abstract: Aims: Decisions about deactivation of implantable cardioverter defibrillators (ICDs) are complicated. Unilateral do-not-resuscitate (DNR) orders (against patient/family wishes) have been ethically justified in cases of medical futility. Unilateral deactivation of ICDs may be seen as a logical extension of a unilateral DNR order. However, the ethical implications of unilateral ICD deactivation have not been explored. Methods and results: Sixty patients who had an ICD or cardiac resynchronization therapy with defibrillator (CRT-D) were interviewed at a quaternary medical centre outpatient electrophysiology practice. Survey questions addressed whether deactivation of defibrillator function was included in advanced directives, whether deactivation constitutes physician-assisted suicide, and whether unilateral deactivation can be ethically justified. Responses were elicited to scenarios in which defibrillation function was deactivated in different contexts (including patient request to deactivate, existing DNR, and unilateral deactivation). Only 15% of respondents had thought about device deactivation if they were to develop a serious illness from which they were not expected to recover. A majority (53%) had advance directives, but only one mentioned what to do with the device. However, a majority (78%) did not consider deactivation of an ICD shocking function against patients' wishes to be ethical or moral. Conclusion: Management of ICDs and CRT-Ds as patients near the end of their lives creates ethical dilemmas. Few patients consider device deactivation at end-of-life, although a large majority believes that unilateral deactivation is not ethical/moral, even in the setting of medical futility. Advance care planning for these patients should address device deactivation.